Faktor yang Mempengaruhi Ketersediaan Obat Program Rujuk Balik (PRB) di Fasilitas Pelayanan Obat PRB Wilayah Eks Karesidenan Kediri (Studi pada Ketersediaan Obat Hipertensi) - Sri Dias Tuti; Umi Athiyah; Wahyu Utami (JURNAL ILMU KEFARMASIAN INDONESIA, 2018)
PRB drugs service was given to chronically patients who still need long term treatment therefore there was need to guarantee the availability of medicines for their therapeutic needs. The objectives of this research were to know about PRB drug management, to know drug management support, policy, the availability of PRB drugs, and to analize the effects of drug management, drug management support, and policy on drug availability in PRB drug facility in Ex Karesidenan Kediri. Study on the availability of drugs hypertension due to prevalence of hypertension disease tends to increase from 7.6% in 2007 to 9.5% in 2013. This research used cross sectional approach by giving questionnaires to 18 respondents of PRB drug managers who had fulfilled the inclusion criteria. Those respondents were measured on the capability in PRB drug managements and assessment of PRB drug management support and policy. The questionnaires were valid and reliable. The management, management support, and policy score were tested for effect on PRB drug availability for Hypertension by using multiple linear regression. From this research, it was known that PRB Drug Management, PRB Drug Management Supporting Assessment, and PRB Policy by PRB drug managers in drug service facilities in Ex Karesidenan Kediri were mostly categorized as good enough. The availability of PRB drugs at PRB drugs facility with stock calculations indicated the ability to provide PRB medication to serve PRB prescription of hypertension was 28.71%. While the facilitieas that were able to serve an average of 72.67, thus providing substitution drugs beyond the average of PRB stock of 43.95%. The efforts were done for examples, borrowed similar drugs from regular supplies, medicines administered when they were available, or established the similar drugs at prices closed to e-catalogue. The results of the analysis showed that simultaneously PRB Drug Management factors, PRB Drug Management Supports, and PRB Policy have significant effects on PRB Drug Availability (p<0.10). PRB drug management had the greatest effects on the availability (p<0.10), especially in the case of Drug Selection (p<0.10). Selection of drugs was the first step to be done from a cycle of drug management, where the early step was the step that most determine the next steps. The pharmaceutical management framework affected the availability of PRB drugs, particularly the Drug Management factor, especially in the drug selection step. Drug selection was an early step of the drug management cycle that determined the next step.